Sanções tributárias: uma visão constitucional - Cruz, Michelle Marie Caldas (2009)
The present work has the aim to study tributary sanctions in the light of the Federal Constitution, analyzing the limits of the punitive power of the State. Therefore, a doctrinal review was made about the juridical norms theories and the concept of sanction. Sanction, in its basic meaning, is considered a penalty. We defend the existence of a unique Punishment Law, based on constitutional principles and in the least intervention of criminal law. We work in the distinction between illicit tributary and tributary crime, between tributary fee and fee due to fiscal crime, pondering about the accumulation of penalties in the criminal and tributary law, showing the differences between insolvency and fiscal evasion. We also emphasize the question of the lack of a legal device that regulates indexation and its application through the Selic index